Critical Discourse Analysis on Lagu Untuk Pak Bupati a Study of Banyumas Regional Head Election - Rosdiana Puspita Sari; Gigih Ariastuti Purwandari; Chusni Hadiati; Eni Nuraeni (Jurnal Lingua Idea, 2020)
Regional head election in Indonesia has successfully conducted in June 27, 2018. It is a kind of people democratic party which is held in most parts of Indonesia regions. Many ways have been conducted by those who were nominated to the position. Language as a means of communication takes important role in this agenda. Regional head election becomes popular theme in several songs to promote candidates. This language phenomenon is interesting since the songs does not merely show its lyrics but it also display power. Critical Discourse Analysis gives makes it possible to reveal the relation between language and power. This article shows how language exhibit power through three levels of CDA that contain linguistic feature, text production, and social practice. Keyword : Song, regional head election, critical discourse analysis, social practice, text production